Aerosol trace metal concentration and dissolution characteristics from known dust emitters in southern Africa - Kangueehi, Kaukurauee Ismael (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.